Spectral analysis of gas dynamic processes in the inlet system of a piston engine with turbocharger - L. V. Plotnikov; Y. M. Brodov; B. P. Zhilkin; D. S. Shestakov; L. E. Osipov (Известия высших учебных заведений: Проблемы энергетики)
THE PURPOSE. To carry out a comparative analysis of the spectra of gas-dynamic characteristics of flows in the intake systems of piston engines with and without turbocharging, to assess the degree of influence of the turbocharger on the flow structure in such systems, and also to propose a method for the gas-dynamic improvement of processes in the system under consideration. METHODS. Due to the complexity of the object of research, an experimental approach was taken as a basis. The experiments were carried out on a single-cylinder piston engine model, which could be equipped with a turbocharger. A system for collecting and processing experimental data based on an analog-to-digital converter was used in the study. Data on changes in local values of velocity and static pressure of pulsating flows in the intake system during the engine's operating cycle were obtained using a constant temperature hot-wire anemometer and a fast-acting pressure sensor. Spectral analysis of functions of flow velocity and pressure versus time was carried out on the basis of the fast Fourier transform algorithm.RESULTS. The article presents a comparative analysis of the spectra of the amplitudes of the velocity and pressure pulsations in the intake system of an engine with and without turbocharging. Also proposed is a method for stabilizing the pulsating flow in the intake system by installing a leveling grid in the outlet channel of the turbocharger compressor. CONCLUSION. It is shown that the installation of a turbocharger leads to a significant change in the structure of gas flows in the intake system of the engine. It has been established that the presence of a leveling grid in the intake system of a turbocharged piston engine leads to a decrease in the low-frequency amplitudes of the flow velocity and pressure pulsations up to 30%. It is shown that the probability of failure-free operation of an automobile engine (cylinder diameter – 82 mm, piston stroke – 71 mm) increases by almost 1% when a leveling grille is used in the intake system.